L’évolution démographique en Andorre est-elle compatible avec le maintien de son identité culturelle ? - Jérôme Tourbeaux (Espace populations sociétés, 2011)
The Principality of Andorra is a microstate located in the heart of the Pyrénées-Orientales, mountain range between Spain and France. It is one of the smallest countries in the world, both from a geographical and demographic point of view.The population of Andorra has the distinction of being largely composed of non-Andorran. Therefore, political rights such as voting rights are held by a minority who has the power to make decisions for all communities that form the Andorran society. This situation, which can cause conflict and resentment, can be explained by strong migration flows that have marked the principality during its economic boom, combined with restrictive legislation on access to nationality. Today, the Andorran authorities are trying to integrate these people by letting them acquire the primary marker of identity of the principality : the Catalan language, while facilitating access to citizenship of children born in Andorra from foreign parents. At the time of the debate on national identity in France, it would seem interesting to show how Andorra handles this sensitive issue.